2010
DOI: 10.1097/dbp.0b013e3181f17c52
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Comparing Traumatic Stress Symptoms by Child and Parent Report Across Pediatric Chronic Illness Groups

Abstract: Objective-Researchers have recently used a framework of traumatic stress to describe the psychological functioning of children experiencing a chronic illness and their families; however, few studies are available directly comparing symptoms across disease groups. The current study compared traumatic stress symptoms of youth being considered for solid organ and bone marrow transplantation, youth diagnosed with Human Immunodeficiency Virus (HIV), youth diagnosed with sickle cell disease (SCD) and their parents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…As parental attunement and potential bias have received considerable attention as sources of discrepancy in parent–child reporting (Ghesquire et al, 2008; Ingerski et al, 2010; Shemesh et al, 2005), several important findings from this study are worth highlighting. First, the positive correlation between parent and child informants on total PTSD symptoms measured at pretreatment appeared to be relatively stronger than those previously found in non-clinical samples.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As parental attunement and potential bias have received considerable attention as sources of discrepancy in parent–child reporting (Ghesquire et al, 2008; Ingerski et al, 2010; Shemesh et al, 2005), several important findings from this study are worth highlighting. First, the positive correlation between parent and child informants on total PTSD symptoms measured at pretreatment appeared to be relatively stronger than those previously found in non-clinical samples.…”
Section: Discussionmentioning
confidence: 84%
“…Frequently, parents own symptomatology has been considered as a potential factor that may bias parent-report of child psychopathology. Indeed, several studies have linked parent self-reported PTSD symptoms with their report of their child's symptoms (e.g., Ghesquire et al, 2008; Ingerski et al, 2010; Shemesh et al, 2005), perhaps reflecting that traumatic events are often experienced by multiple members of a family. Given our findings, caution is urged before attributing informant discrepancies to parental bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1821 There is more information about parent caregivers of children undergoing HCT or solid organ transplantation; in one such study 14% of caregivers and 15% of children self-reported PTSD. 22 …”
Section: Introductionmentioning
confidence: 99%
“…1 The United States is faced with a rate of 19.3% of children with special health care needs, 2 among which include those with diagnosis of a chronic disease, which accounts for 42% of health care costs for the child population. 3 In Brazil, research reveals that 9.1% of children aged zero to five years present with chronic diseases, as well as 9.7% of schoolchildren between six and thirteen and 11% of adolescents aged fourteen to nineteen years of the general total population.…”
Section: Introductionmentioning
confidence: 99%